Low‐residue diet fed to rabbits induces histomorphological and biomechanical remodeling of small intestine. Issue 4 (27th October 2016) - Liu, Y.; Zhao, J.; Liao, D.; Bao, L.; Gregersen, H.
Abstract: Background: The composition of ingested food is important for the gut microbiome and intestinal homeostasis. We have previously demonstrated that the structure and mechanical properties in the small intestine remodel significantly during fasting. However, it is not clear to what extent the intestinal mechanical properties changes when the composition of food is changed. This study aimed to investigate the passive biomechanical properties and intestinal tissue remodeling in rabbits fed a low‐residue diet. Methods: New Zealand rabbits (control group n=6, intervention group n=7) were studied. Segments from duodenum, jejunum and ileum were excised. The intestinal diameter and length were obtained from digitized images of the segments at preselected luminal pressure levels and at no‐load and zero‐stress states. Circumferential and longitudinal stresses (force per area) and strains (deformation) were computed from the length, diameter and pressure data referenced to the zero‐stress state geometry. Histomorphometric data were also obtained. Key Results: The wet weight‐per‐unit length, wall thickness and wall area decreased in the intervention group ( P <.05, P <.01). Histological measurement confirmed that the wall thickness decreased in all three segments, which was primarily due to mucosal thinning ( P <.05). The opening angle tended to increase in all segments in the intervention group. Significant difference between the two groups was found for the jejunum ( P <.05). Feeding the low‐residue diet shifted the circumferential stress‐strain curves in the intervention group to the right, indicating intestinal wall softening. Conclusions & Inferences: Low‐residue diet in rabbits for 1 month induces location‐dependent histomorphometric and biomechanical remodeling of the intestine. Abstract : This study demonstrated that low‐residue diet in rabbits for one month induces intestinal histomorphometric and biomechanical remodelling, specifically mucosal changes and intestinal softening. The intestine is a complex mechanical organ. It is important to consider food‐induced changes to all aspects of intestinal function.